Chlorpyrifos-induced oxidative damage is reduced under warming and predation risk: Explaining antagonistic interactions with a pesticide. (July 2017) - Janssens, Lizanne; Stoks, Robby
Abstract: Interactions with pollutants and environmental factors are poorly studied for physiological traits. Yet physiological traits are important for explaining and predicting interactions at higher levels of organization. We investigated the single and combined impact of the pesticide chlorpyrifos, predation risk and warming on endpoints related to oxidative stress in the damselfly Enallagma cyathigerum . We thereby integrated information on reactive oxygen species (ROS), antioxidant enzymes and oxidative damage. All three treatments impacted the oxidative stress levels and for most traits the pesticide interacted antagonistically with warming or predation risk. Chlorpyrifos exposure resulted in increased ROS levels, decreased antioxidant defence and increased oxidative damage compared to the control situation. Under warming, the pesticide-induced increase in oxidative stress was less strong and the investment in antioxidant defence higher. Although both the pesticide and predation risk increased oxidative damage, the effects of the pesticide on oxidative damage were less strong in the presence of predator cues (at 20 °C). Despite the weaker pesticide-induced effects under predation risk, the combination of the pesticide and predator cues consistently caused the highest ROS levels, the lowest antioxidant defence and the highest oxidative damage, indicating the importance of cumulative stressor effects for impairing fitness. Our results provide the first evidence for antagonistic interactions of warming and predation risk with a pollutant for physiological traits. We identified two general mechanisms that may generate antagonistic interactions for oxidative stress: cross-tolerance and the maximum cumulative levels of damage. Graphical abstract: Highlights: Co-exposure to pesticides, warming and predators is common in nature. Chlorpyrifos increased ROS and oxidative damage and decreased antioxidant defence. Animals coped better with the pesticide when reared at higher temperatures. The predator cues lowered the pesticide-induced increase in oxidative damage. Cross-tolerance and maximum damage levels may explain antagonistic interactions. Abstract : Chlorpyrifos induces oxidative stress and interacts antagonistically with warming and predation risk due to cross-tolerance and maximum levels of damage animals can cope with.